NOMADIC PASTORALISM AND THE PREVALENCE OF PULMONARY TUBERCULOSIS (TB) IN THE NORTH-WESTERN REGION OF NIGERIA (2014)
The pattern of human mobility affects the spread of infectious diseases, particularly tuberculosis (TB), the transmission which is associated with several factors, including the consumption of unpasteurised milk. However, the very few studies that have been conducted on the role of seasonal migration on disease transmission are inconclusive. In particular, the transmission of TB along seasonal migration routes in Nigeria has not been given adequate attention. This study, therefore, examined the prevalence of pulmonary TB in the North-western region of Nigeria. Using a survey design, disease ecology and distance decay effect provided the framework. Purposive and random sampling techniques were used to collect data from the records of 15 Directly Observed Therapy Short-course (DOTS) each along and off-route centres. A structured questionnaire was administered to 461 (26.6%) proportionately and randomly selected patients receiving treatment. Data were collected on the socio-demographic (gender, age, marital status, population size, work history, occupation type, income and literacy levels), behavioural (visits to health centre to treat TB, smoking, consumption of unpasteurised milk profiles and perceived causes of TB), and environmental (history of infection with TB, access to healthcare and exposure to dust) factors. Data were also collected on distance (determined from topographical maps) along and off-route TB centres, duration of stay in a place and number of health facilities. Population figures were projected from 1991 population census results to 2010. Students t-test, Simple Linear Regression, Correlation and Analysis of Variance were used for data analyses at p?0.05. Sixty-five percent of the respondents were male and 161 (34.9%) female respondents; 29.0% had a job while 39.3% had no formal education, 35.0% had visited clinics to treat TB, 35.0% consumed unpasteurized milk and 28.0% smoked cigarettes. Infection (35.1%), dust (14.1%), smoking (12.1%), spiritual attacks (10.4%), drinking of cold water (10.0%) and unpasteurized milk (1.5%) were the perceived causes of TB. Whereas, 47.7% had TB, 39.2% were exposed to dust, 9.2% family members were infected, 6.4% had lung diseases and 8.5% stayed with infected persons. Cost (45.3%), attitude of health personnel (13.4%), time (13.0%) and distance (9.7%) were the determinants of access to healthcare. Gender (t=2.1), marital status (t=4.0), work experience (t=2.8) and work type (t=-3.2) were significant in TB prevalence. Lung diseases (?=4.9), spiritual attack (?=4.3), farming (?=4.0) and distance to healthcare centres (?=3.7) positively contributed to TB prevalence while distance along (r=-0.17) and off-route (r=0.11), and duration of stay did not. Similarly, TB prevalence had a strong positive relationship with population size (r=0.76) and number of health facilities (r=0.87). Month of the year affected TB prevalence among off-route centres [F(26,153)=2.06], whereas income [F(17,57)=5.40], literacy [F(20,24)=5.15] levels, and work duration [F(11,48)=2.77] affected prevalence along the route. Tuberculosis was more prevalent during the dry season (November-April) and reduced southwards. Human mobility did not substantially affect tuberculosis prevalence in North-western region of Nigeria. However, continuous monitoring and control of the disease within the region is required.